Phenotype-based screening of the melanogenic effects of selected mangrove methanolic crude extracts using zebrafish (Danio rerio) as a model - Grisola, Mark Andre C. (2016)
There is a rising trend in developing novel hypopigmenting agents due to the unwanted side effects of existing therapies and treatments. In this study, the melanogenic effects of the crude extracts of selected mangroves namely Avicennia marina, Excoecaria agallocha, Rhizophora apiculata, and Sonneratia alba were screened using zabrafish as the model organism. During the screening process, 50 ug/mL and 100 ug/mL concentration of the extracts were applied on the zebrafish embryos at 9 hours post fertilization (hpf) and effects were observed at 55 hours post fertilization (hpf). Results showed that all extracts had only none or mild effects on the melanogenesis of the embryos. Some extracts showed toxicity to the embryos. Among the extracts, S. alba bark displayed the relatively best results in terms of its effect on melanogenesis and toxicity. It was further investigated and was found to have a dose-dependent effect on the pigmentation of embryos. Higher dosages of S. alba bark extract such as 400 ug/mL and 500 ug/mL caused profound effects on the melanogenesis of the embryos. ImageJ Analysis revealed that higher dosages remarkably decreased the ocular melanin content of the embryos. One-way ANOVA also revealed that the mean difference in ocular melanin content of embryos from different dosage groups was statistically significant (F(6,63) = 126.513, p <0.001). The highest dosage, 500 ug/mL, was the most effective dosage in decreasing the pigmentation of the embryos. The active compounds lupeol and 3,3'-di-O-methylellagic acid present in the S. alba bark extract may have inhibited the melanogenesis in zebrafish embryos.